Properties of kenaf fiber-reinforced polyamide 6 composites - Abdullah, Norihan; Abdan, Khalina; Mohd Roslim, Muhammad Huzaifah; Radzuan, Mohd Nazren; Shafi, Ayu Rafiqah; Hao, Lee Ching (De Gruyter, 2024)
Despite the increasing interest in polyamidebased composites, few studies on polyamide-based natural fiber composites have been conducted due to their high melting temperatures of polyamide 6 (PA6). In this study, kenaf fiber-reinforced polyamide 6 composites (KF/PA6) were successfully prepared and their properties were investigated. Thermogravimetric analysis demonstrated that the neat PA6 has higher thermal stability with higher melting temperatures of 426°C, respectively, than KF/PA6 composites. The results of the differential scanning calorimeter showed that the glass transition temperature (Tg) of KF/ PA6 composites was slightly shifted to a higher temperature at 59°C than that of the neat PA6 at 45°C. The thermal and mechanical characteristics using dynamic mechanical analysis results showed that the storage and loss modulus of the neat PA6 were higher than those of KF/PA6 composites. The neat PA6 showed the maximum tensile strength of 48 MPa; however, the maximum tensile modulus was obtained at 10 wt% KF with 2,100 MPa. The flexural strength and modulus of the neat PA6 were 91 and 2,506 MPa, respectively, which were higher than those of KF/PA6 composites. The impact strength also deteriorated with the addition of KF, from 3.72 to 1.91 kJ·m−2 . Voids, fiber pulled-out, and agglomeration were observed in scanning electron microscope analysis on the tensile fractured surfaces.